PENGARUH METODE PENYEDUHAN TERHADAP KARAKTERISTIK ORGANOLEPTIK KOPI ROBUSTA DAN LIBERIKA - Dewi, Rahmi Dewi Harahap (JURAGAN - Jurnal Agroteknologi, 2025)
Abstract This study aims to evaluate the effect of brewing methods using French Press, Syphon, and Moka Pot on the organoleptic characteristics of Robusta and Liberica coffee. The parameters tested include color, taste, aroma, clarity, and after taste. The results showed that the Syphon method gave the best results in terms of aroma and clarity, while the Moka Pot produced the most concentrated coffee color. However, after taste tended to be low in all methods. Choosing the right brewing method is important to optimize coffee quality according to consumer preferences.